Software testing - Patton, Ron (Sams Pub., 2005)
Software Testing, Second Edition provides practical insight into the world of software testing and quality assurance. Learn how to find problems in any computer program, how to plan an effective test approach and how to tell when software is ready for release. Updated from the previous edition in 2000 to include a chapter that specifically deals with testing software for security bugs, the processes and techniques used throughout the book are timeless. This book is an excellent investment if you want to better understand what your Software Test team does or you want to write better software.